Hypothermia theraphy in patients post cardiac arrest - Yudha, Tria; Prasetya, Indra; Tjahjono, Cholid Tri; Anjarwani, Setyasih (Heart Science Journal, 2025)
Cardiovascular disease is the leading cause of death in several developing countries, and many of these deaths occur before reaching the hospital due to cardiac arrest. Most patients who return to spontaneous circulation (ROSC) and are brought to the hospital experience severe neurological damage during cardiac arrest, and this damage is the cause of in-hospital mortality. Improvements in survival and neurologic improvement of patients with CA have focused on two main therapy areas. The first area is improved education and skills of medical and paramedical personnel to improve perfusion post CA. The second area is a greater emphasis on post-resuscitation care which includes optimizing oxygenation and ventilation, avoiding hypotension, treating causes of CA such as acute coronary ischemia, and initiating hypothermia therapy if necessary, as in the 2020 guidelines and recommendations from the American Heart Association (AHA), International Liaison Committee of Resuscitation, and European Resuscitation Council covering the entire spectrum of post-resuscitation care.  The AHA guidelines 2020 recommend optimizing hypothermia therapy for 24 hours with a target temperature between 320C - 360C in ROSC patients to improve clinical outcomes of neurological status after cardiac arrest. This is contrast to the study of Martinell et al in their research which concluded that there was no significant difference in survival rates within 30 days after cardiac arrest in patients who received either hypothermia therapy or those who did not. Hypothermia therapy, which is currently part of the post-resuscitation care recommendations, has varied variables and remains controversial in its implementation. Based on this, this referent will discuss the effects of hypothermia therapy on post-cardiac arrest patients, the stages, and the practical aspects of implementing hypothermia therapy.